Teenage aggression, causes and risk factors - M.F. Denisova; N.M. Musyca; Z.A. Shkiryak-Nizhnik (Zaslavsky O.Yu., 2019)
Background. Children's health could be described as a state of life, corresponding to the biological age of the child, the harmonic functioning of the body systems and its relationship with the environment as well as the unity of psychomotor and intellectual characteristics. The number of minors with aggressive behavior is growing from year to year that is revealed in antisocial actions - violation of public order, hooliganism, vandalism. Changes in the structure of nutrition are considered as a serious risk factor for adolescent health. From the point of view of today's realities, irrational nutrition can be not only a factor in the formation of anorexia and bulimia but also a breeding ground for aggressive behavior of children. This study purpose was to find the relationship between the aggressive behavior of adolescents and possible factors of its improvement. Materials and methods. The study is based on the information collected through international program ELSPAC (European Longitudinal Study of Parenthood And Childhood - European long-term monitoring of paternity and childhood), its Ukrainian fragment "Family and Children of Ukraine". This research was focused on an analysis of the database from two separate groups: adolescents having signs of aggressive behavior and adolescents without aggressive signs. A relational database was formed for 864 adolescents of 15-18 years old. Results. A number of indicators of eating behavior have been analyzed, and some risk factors for the development of aggression have been identified. Reliably significant indicators of the difference in the nutritional behavior of adolescents of aggressive and non-aggressive groups have been revealed. Adolescents of aggressive group, even after receiving information about violation of eating habits, did not visit doctor or neglected such advice. Uncontrolled eating, refusal to eat poultry, fish, egg, frequent consume of junk food, use of energy drinks twice times a week or more often were typical for them. Most of vegetarians are teenagers from aggressive group. Teenagers from non-aggressive group were significantly more likely to have the correct diet - no uncontrolled food cravings, hot meals three times a day, their diet include poultry, fish, egg, and minimum consume of fast food.